ByzRev 03.2021.003: Athanassios Mailis, Obscured by Walls. The Bēma Display of the Cretan Churches from Visibility to Concealment: (Byzanz zwischen Orient und Okzident 18). Regensburg: Schnell & Steiner 2020. - Altripp, Michael (The Byzantine Review, 2021)
Athanassios Mailis, Obscured by Walls. The Bēma Display of the Cretan Churches from Visibility to Concealment (Byzanz zwischen Orient und Okzident 18). Regensburg: Schnell & Steiner 2020. 156 S. – ISBN: 978-3-7954-3560-8 (EUR 39.00)